Trajectories of adherence to an obesogenic dietary pattern and changes in diet quality, food intake, and adiposity during adolescence - Jesús Martínez-Gómez; Patricia Bodega; Gloria Santos-Beneit; Amaya de Cos-Gandoy; María Beneito-Durá; Mercedes de Miguel; Anna Tresserra-Rimbau; Ana María Ruiz-León; Ramón Estruch; Rosa María Lamuela-Raventós; Luis A. Moreno; Juan Miguel Fernández-Alvira; et al. (Nutrition Journal)
Abstract Background and Aims Contemporary longitudinal data on dietary patterns (DP) during adolescence are scarce. This study aimed to identify trajectories of adherence to an obesogenic DP and changes in diet quality (DQ), related food consumption, and adiposity markers during adolescence. Methods A cohort of 600 adolescents (293 girls, 48.8%) attending 24 secondary schools enrolled on the SI! Program for Secondary Schools trial in Spain was assessed when participants were approximately 12, 14, and 16 years old. An energy-dense, high-fat, and low-fiber (obesogenic) DP was derived at each time point by reduced rank regression (RRR) using the percentage energy intake from fat, fiber density, and dietary energy density as intermediate variables. Based on each participant's resulting scores, trajectories of adherence to the obesogenic DP were identified by latent class trajectory modeling. Adjusted associations between trajectories, DQ and food consumption changes, and adiposity markers during adolescence were analyzed with generalized linear models. Results Based on adherence to the obesogenic DP during adolescence, four stable trajectory groups (from lowest to highest adherence) were identified: trajectory 1 (44 participants [7.3%]), trajectory 2 (180 participants [30.0%]), trajectory 3 (292 participants [48.7%]), and trajectory 4 (84 participants [14.0%]). Overall DQ was moderate, but showed a gradient across trajectories, with trajectory 1 having the best quality. Although the identified trajectories were stable, individuals in the group with the lowest adherence to the obesogenic DP (trajectory 1) significantly improved their overall DQ over time, whereas those with the highest adherence (trajectory 4) showed the opposite trend. The group of adolescents in trajectory 4 had the least healthy central adiposity profile when ∼16 years old. Conclusion Four stable trajectories of adherence to an obesogenic DP were identified in a large cohort of adolescents, with DQ decreasing as adherence to the DP increased. Although adherence to the DP was stable, differences in food intake between trajectories widened over time, resulting in increased central adiposity in participants with the highest adherence to the pattern at the end of the study. Further research is needed to explore the determinants of adherence to obesogenic DPs in adolescence and to evaluate their effects on adiposity and overall health later in life. Trial registration ClinicalTrials.gov NCT03504059.